2015
DOI: 10.1634/theoncologist.2014-0265
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Addressing the Needs of Adolescents and Young Adults With Cancer: Summary of an Institute of Medicine Workshop

Abstract: Cancer is the leading disease‐related cause of death in adolescents and young adults (AYAs). This population faces many short‐ and long‐term health and psychosocial consequences of cancer diagnosis and treatment, but many programs for cancer treatment, survivorship care, and psychosocial support do not focus on the specific needs of AYA cancer patients. Recognizing this health care disparity, the National Cancer Policy Forum of the Institute of Medicine convened a public workshop to examine the needs of AYA pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
201
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(216 citation statements)
references
References 69 publications
(70 reference statements)
5
201
0
6
Order By: Relevance
“…15 The distinct biology of disease and age-related issues in AYA patients should be considered in the treatment decision-making process. 16 The AYA patient is generally defined as an individual 15 to 39 years of age at the time of initial cancer diagnosis. 6,17 Nearly 70,000 people in this age group are diagnosed with cancer each year in the United States, which is more than 7 times more people than are diagnosed at younger than 15 years of age.…”
Section: Palliative Care and End-of-life Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 The distinct biology of disease and age-related issues in AYA patients should be considered in the treatment decision-making process. 16 The AYA patient is generally defined as an individual 15 to 39 years of age at the time of initial cancer diagnosis. 6,17 Nearly 70,000 people in this age group are diagnosed with cancer each year in the United States, which is more than 7 times more people than are diagnosed at younger than 15 years of age.…”
Section: Palliative Care and End-of-life Considerationsmentioning
confidence: 99%
“…[34][35][36] As mentioned earlier, the low rate of participation in clinical trials is one of the main reasons for the lack of improvement in outcomes in AYA patients with cancer. 1,3,4,22 A review of 30 studies of adolescents with cancer (ages [15][16][17][18][19] showed that 5% to 34% of these patients enrolled in clinical trials. 22 In 20 to 25 year olds, clinical trial enrollment further decreases to approximately 2%.…”
Section: Age-appropriate Carementioning
confidence: 99%
See 1 more Smart Citation
“…Along with rising cancer incidence in this age group, this disparity has led to an increased interest in their unique needs. Independence, school, partner, family, and career choices are just a few of the milestones that occur during this developmental stage [2,3]. Cancer can disrupt these developmental tasks-necessitating dependence where independence was emerging, putting school and career goals on hold, dictating treatments that challenge intimacy and fertility-resulting in short and long-term effects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cancer was the leading cause of death due to illness in the adolescent and young adult (18-39 year old) population [2]. Despite these figures, no one thinks he is close to suffering from cancer.…”
Section: Manuscript Organizationmentioning
confidence: 99%